Sin and evil in African Christian theologies: A classification - Conradie, EM (Nederduitse Gereformeerde Teologiese Tydskrif, 2006)
This article is based on the observation that there is a tension between an affirmation of the inherent goodness of humanity and the widespread prevalence of corruption in Africa. In African traditional culture, there is a tendency to regard human wrongdoing (sin) as the product of external evil forces beyond the control the individual. By contrast, there has been a tendency in Western Christianity to regard evil as the product of sin, understood as alienation from God. This contribution is based on a bibliographic survey of how African Christian theologians relate such traditional African thought patterns with Christian convictions. It offers a classification of the ways in which the relationship between sin and evil is understood in enculturation theologies, liberation theologies, Pentecostal theologies, by Zionist churches and in evangelical theologies in the African context.